The Quality of Earnings Reported in Financial Statements of Capital Groups - Comporek, Michał (Journal of Finance and Financial Law, 2023)
The purpose of the article. The paper’s main aim is a six-factor analysis of earnings quality in financial statements of public companies belonging to capital groups and listed on the Main Market of the Warsaw Stock Exchange. Methodology. The category of earnings quality as estimated considering the discretionary accruals and current discretionary accruals coefficients, the ratio of conditional conservatism and indicators of stability, predictability or smoothness of the net financial result. Empirical research was conducted among 230 non-financial listed companies whose shares were traded in 2011–2021. The research methodology is based on the use of the Modified Jones model (1995), Dechow and Dichev model (2002), An model (2017), as well as statistics of the distribution of variables, Mann-Whitney-Wilcoxon test or Wilcoxon signed ranks test. Results of the research. The empirical analyses proved that public companies not belonging to capital groups implement accrual-based earnings management practices to a greater extent than companies operating within these groups. Earnings quality in the consolidated statements is generally higher than the quality of profits (losses) appearing in the separate statements of the business units performing a superior function within individual capital groups.